2013
DOI: 10.5578/mb.4970
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical and Laboratory Findings of Pediatric Patients with Adenovirus-Associated Respiratory Tract Infections

Abstract: Upper respiratory tract infections caused by adenoviruses present long lasting fever for five days and elevated acute phase reactant levels. They are generally misdiagnosed as bacterial infections and are mistreated with antibiotics. The diagnosis of adenovirus infections mainly depends on direct antigen tests, virus isolation and detection of viral DNA using polymerase chain reaction (PCR). The aim of this study was to evaluate the clinical and laboratory findings of the children diagnosed as adenoviral respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…Laboratory findings of HAdV infections include elevated CRP, leukocytosis, and neutrophilia. 37 In our study, HAdV had significantly longer fever duration (5.60 AE 0.54 days) and elevated CRP level (3.53 AE 4.51 mg/ dl).…”
Section: Discussionsupporting
confidence: 48%
“…Laboratory findings of HAdV infections include elevated CRP, leukocytosis, and neutrophilia. 37 In our study, HAdV had significantly longer fever duration (5.60 AE 0.54 days) and elevated CRP level (3.53 AE 4.51 mg/ dl).…”
Section: Discussionsupporting
confidence: 48%
“…In addition, it was noted that HMPV and HBoV infections were mostly observed in the 2-5 year age group and AV infections were mostly observed in children aged above 5 years in our study, though statistical significance was not present. In a study conducted in our country in which 27 cases of AV-related respiratory infection were examined, it was reported that the patients were mostly aged 4 years and older (22). In another study, it was reported that AV infections were found at older ages compared to RSV infections (mean age, 41 months, 23 months) (23).…”
Section: Discussionmentioning
confidence: 99%
“…Although most pediatric adenovirus (ADV) respiratory infections are considered milder, the disease can be severe in some children and can even result in substantial morbidity7. Adenoviruses have been reported to account for 2–5% of overall respiratory illnesses and 4–10% of pneumonia cases8. However, these causative agents cannot be differentiated based on clinical symptoms alone.…”
mentioning
confidence: 99%